Pembelajaran PAI dengan Metode Mind Mapping dalam Peningkatan Kreativitas Siswa di Sekolah Menengah Pertama - Furqon, Zenal (Epistemic: Jurnal Ilmiah Pendidikan, 2022)
The importance of creative teaching methods has become a focal point in enhancing student engagement and learning outcomes. This study aims to investigate the impact of the mind mapping model on the creativity of students in PAI Hajj and Umrah materials. Utilizing a pre-experimental design with a one-group pretest-posttest methodology, the research involved 26 ninth-grade students from Daarut Tauhiid Junior High School, Bandung, in the 2022-2023 academic year. Data were analyzed using the Wilcoxon test. Findings revealed a significant increase in the average learning outcomes, with a difference score of 14.00 between pretest and posttest results, and a sig value of 0.00 < 0.05, indicating a positive effect of the mind mapping model on student creativity. These results underscore the potential of mind mapping in fostering creativity and improving educational outcomes in Islamic Religious Education. The implications suggest that educators should consider incorporating mind mapping techniques to enhance student engagement and learning effectiveness.